2014
DOI: 10.1182/blood-2014-03-559815
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 and MPL protein levels determine TPO-induced megakaryocyte proliferation vs differentiation

Abstract: • We propose that megakaryopoiesis is regulated by the expression levels of the TPO receptor MPL and the associated tyrosine kinase JAK2.• This model could explain why suboptimal doses of JAK2 inhibitors can induce a paradoxical increase in platelet production.Megakaryopoiesis is a 2-step differentiation process, regulated by thrombopoietin (TPO), on binding to its cognate receptor myeloproliferative leukemia (MPL). This receptor associates with intracytoplasmic tyrosine kinases, essentially janus kinase 2 (JA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 34 publications
(47 reference statements)
3
39
0
Order By: Relevance
“…This could be explained by the fact that the MPL homozygous sub‐clone emerged recently and that this clone size will increase in the future. An alternative hypothesis could be in accordance with our previous study suggesting that the higher the MPL signalling, the lower the proliferative advantage . In this case, the homozygous mutated MPL clone would not have proliferative advantage compared with the heterozygous MPL mutated clone.…”
Section: Resultssupporting
confidence: 86%
“…This could be explained by the fact that the MPL homozygous sub‐clone emerged recently and that this clone size will increase in the future. An alternative hypothesis could be in accordance with our previous study suggesting that the higher the MPL signalling, the lower the proliferative advantage . In this case, the homozygous mutated MPL clone would not have proliferative advantage compared with the heterozygous MPL mutated clone.…”
Section: Resultssupporting
confidence: 86%
“…44 Similarly, using UT7-MPL cell lines, Besancenot et al showed that low levels of MPL expression increased TPO-stimulated proliferation, whereas low doses of JAK2 chemical inhibitors caused increased platelet production in mice. 45 It would appear that some of these data contradict our findings that reduced Mpl expression prevents JAK2V 617 F-mediated myeloproliferation. However, there are a number of differences between the studies that may explain the varying results.…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, some studies suggest that an incomplete JAK2 inhibition and JAK2/MPL deletion in megakaryocytes and platelets may induce a paradoxical increase in platelet production [8][9][10]. Accordingly, we can hypothesize that in our patient, quantitative/qualitative abnormalities of the MPL receptor/signaling pathway may occur in megakaryocytecommitted progenitor cells and/or in megakaryocytes, resulting in stimulation of platelet production and thrombocytosis when ruxolitinib-driven JAK2 inhibition contributes to pathway deregulation.…”
mentioning
confidence: 72%